Peran Orang Tua Sebagai Faktor Pendorong Minat Anak Meneruskan Bisnis Keluarga - Putri Rahayu Lestari Hasih; Erica Adriana (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
Children's interest in continuing the family business is an important factor in maintaining business continuity and preserving family heritage. However, the factors that encourage children's interest in being involved in the family business are still important and interesting research areas to be explored (Y.Roborth, 2015). The role of parents in shaping children's interest in continuing the family business has a significant impact. (Cahyadi, 2019) Parents as owners of a family business are not only responsible for managing the business, but also must ensure that the next generation has sufficient interest and motivation to continue the business. Therefore, an understanding of the factors that drive children's interest in continuing the family business is very important.